Luminescence Spectrum of Yttrium Aluminum Garnet Based Phosphors with Initiating by Different Sources of Optical Excitation; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Lisitsyn V. M. Viktor Mikhailovich; Stepanov S. A. Sergey Aleksandrovich; Abdullin H. A. Habibula; Tulegenova A. Aida; Ju Y. Y. Yang Yang; Kolomin V. Viktor (Materials and Technologies in Optoelectronics Production, 2016)
Title screen